The Implication of Pancasila Values on The Renewal of Criminal Law in Indonesia - Dian Alan Setiawan (Universitas Kuningan, 2018)
The current draft of the Criminal Code is inseparable from the idea that the legal characteristics in Indonesia are the adoption of the societys social order which is reflected in the living code of cultural values and social life in Indonesian society which is heterogeneous and plural. The existence of cultural values as a developing law in the society cannot be denied its role in a basic framework for the arrangement of national criminal law in the future. The problem examined in this research is formulated into the following questions: What are the influences of cultural values on the renewal of criminal law? What are the implications of Pancasila values on the development of the current criminal law? The method used in this research was normative legal research method where the law is conceptualized as a method. This research is a legal research using a conceptual and legislation approach that will review the related law. The results of this research provide an understanding to pay attention to the characteristics of criminal law in Indonesia in accordance with the characteristics of Indonesian citizen which is based on the philosophy of Pancasila. It needs to be emphasized since the future renewal of the Criminal Code is expected to be valid in a long term period so that the renewal needs to be done carefully and thoroughly, starting from its substance and structure, legal cultural values, to legal validity. Those aspects should be carefully considered so that the renewal of the Criminal Code is in line with law enforcement efforts which correspond to the societys demands in the reform era. Lastly, this research is expected to provide input to governments, especially to the related lawmakers and law enforcement officers, to make improvements and enhancements in the provisions concerning the influence of Pancasila values on the renewal of criminal law.Konsep Rancangan KUH Pidana yang ada sekarang ini tidak terlepas dari pemikiran bahwa karakteristik hukum di Indonesia merupakan adopsi dari tatanan sosial masyarakat yang tercermin dalam tata laku hidup nilai nilai budaya dan kehidupan sosial dalam keragaman masyarakat Indonesia yang heterogen dan plural. Keberadaan nilai nilai budaya sebagai hukum yang berkembang di masyarakat tidak dapat dipungkiri peranannya dalam suatu kerangka dasar penyusunan hukum pidana nasional di masa yang akan datang. Rumusan masalah yang ditelaah dalam penelitian ini apakah pengaruh nilai nilai budaya terhadap pembaharuan Hukum Pidana ? Apakah implikasi nilai pancasila terhadap perkembangan hukum pidana saat ini ? Metode yang digunakan dalam penelitian ini menggunakan metode penelitian hukum normatif, dimana hukum dikonsepkan sebagai kaedah. Penelitian ini merupakan penelitian hukum dengan menggunakan pendekatan konseptual dan pendekatan perundang-undangan yang akan meninjau kembali Undang-Undang terkait. Hasil penelitian ini memberikan pemahaman agar memperhatikan karakteristik hukum pidana sesuai dengan ciri khas kehidupan masyarakat Indonesia yang hidup berdasarkan falsafah Pancasila. Hal ini perlu ditekankan karena pembaharuan KUH Pidana ke depan diharapkan dapat diperlakukan dalam jangka panjang sehinga perlu digarap dengan cermat dan teliti substansi maupun struktural, nilai budaya hukum, sampai validitas hukum (daya berlaku). semua itu dimaksudkan agar pembentukan KUH Pidana yang baru tersebut tidak menjadi sia-sia dengan upaya penegakan hukum yang sesuai dengan tuntutan masyarakat dalam era reformasi. Simpulan dan saran dalam penelitian ini diharapkan memberi masukkan kepada pemerintah terutama kepada para pembuat undang-undang dan para penegak hukum terkait untuk melakukan penyempurnaan dan perbaikan dalam ketentuan mengenai nilai-nilai pancasila yang memberikan pengaruh terhadap pembaharuan hukum pidana